0828 Positional Central Sleep Apnea. (25th May 2022) - Mempin, Roberto; Sarrami, Kayvon; Thomas, Aaron; Zeidler, Michelle
Abstract: Introduction: Obstructive sleep apnea (OSA) is well known to often improve with non-supine positioning as opposed to supine positioning. The prevalence of OSA that may improve on proper positioning is 50-60% and the prevalence of OSA that appears when supine and disappears when non-supine is 25-30%. Sleeping in a lateral positioning is thought to reduce pressure on the airway, shift the directional effect of gravity on airway structures, and counteract physiologic genioglossus collapse that occurs when supine. On the other hand, the effect of positional changes on the severity of central sleep apnea (CSA) is not well documented aside from Cheyne-stokes breathing in congestive heart failure. Report of Cases: We present two cases of positional CSA. One patient is a 52-year-old male with a history of traumatic brain injury, hypogonadism, hypothyroidism and Parkinson's Disease. He underwent split-polysomnography (PSG) for dream enactment behavior, was found to have severe CSA, which occurred almost exclusively supine (Supine Apnea-Hypopnea Index (AHI) 66/hr, Non-Supine 0.8/hr). A positional belt was recommended to the patient. The second patient is an 89-year-old male with history of chronic obstructive pulmonary disease and chronic kidney disease who underwent PSG for symptoms of sleep apnea. He was found to have severe obstructive and central sleep apnea with periods of Cheyne-stokes breathing. This also occurred almost exclusively supine (Supine AHI 69/hr, Non-Supine 0/hr) and improved on continuous positive airway pressure (CPAP) independent of position (AHI 6/hr). CPAP or positional belt was recommended to the patient. Conclusion: Positional CSA unrelated to congestive heart failure is an uncommon phenomenon with poorly understood pathophysiology. Treatment of CSA is often challenging and based on elucidating and addressing the underlying cause such as optimizing treatment of heart failure. Positional therapy is characteristically thought of as a potential treatment option for OSA. However, our findings further support the presence of a phenotype of central sleep apnea that may respond to positional therapy. Support (If Any):